Perspectives in motion : engaging the visual in dance and music - Stepputat, Kendra; Diettrich, Brian (Dance and Performance Studies, 2021)
"Perspectives in Motion explores visual approaches to performance in global cultural contexts, particularly in as it relates to the work of Adrienne L. Kaeppler, a pioneering researcher who has made a number of interdisciplinary contributions over five decades in dance and performance. Through a diverse range of case studies from Oceania, Asia, and Europe, and interdisciplinary approaches, this edited collection offers new critical and ethnographic frameworks for understanding and experiencing practices of music and dance across the globe"--